PHEROMONAL EFFICACY ON PITUITARY GLAND RELATIG TO REPRODUCTION THROUGH THE NEUROETHO-HYPOPHYSIO GONADAL PATHWAY IN THE FISH CYPRINIS CARPIO - DR. VEENA MAHAJAN, (The Bioscan, 2025)
Conspecifics release chemicals called pheromones, which are known to stimulate spawning behaviour such as eliciting courting, sexual attraction, and spawning readiness. (intraspecific communication) In the current investigation, the fish received weekly injections of 1.5 ml/kg body weight of pheromones for a period of six weeks to the fish, Cyprinus carpio.It has been observed that pheromone showed stimulatory effect which stimulates the sexual behavior and gonadotrophs were increased in number. Consequently, it was determined that pheromone may be utilized as a stimulant in fish breeding in order to attain early maturity and is associated with induction of spawning reflexes in the fish Cyprinus carpio.